Estimation of the cost in a paediatric radiology service using time-driven activity-based costing (TDABC) - Secinaro, Silvana; Brescia, Valerino; Secinaro, Aurelio; Calandra, Davide (Szacowanie kosztów usług radiologii dziecięcej z wykorzystaniem rachunku kosztów działań sterowanego czasem (TDABC), 2021)
Cost estimation is crucial for health accounts analyses in both developed and developing countries. This study aimed to determine a methodology on the issue of costing systems and costing methods applicable to all health services carried out on a large scale that by their nature have a limited variability of resources (time, materials, human resources, etc.). The authors used time-driven activitybased costing (TDABC). The average time of healthcare activities was estimated within the direct observation of the activities and interviews in a paediatric radiology service unit. Direct and indirect costs were calculated regarding the price per minute for each health service category. TDABC allows calculating the actual costs of radiology services. This method reveals a higher expenditure than that reimbursed by the national health service. The empirical study shows high costs for CT and Thoracic spine radiology under sedation, which the national health system does not take into consideration. TDABC can be used by healthcare managers to evaluate the level of costs and to compare the internal results with the reimbursement tariffs from the national health service.
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 2, s. 77-101
Keywords: radiology; costs; drivers; TDABC; healthcare management; radiologia; koszty; nośniki; zarządzanie zdrowiem